High expression of WTAP leads to poor prognosis of gastric cancer by influencing tumour‐associated T lymphocyte infiltration. Issue 8 (16th March 2020) - Li, Huafu; Su, Qiao; Li, Bo; Lan, Linxiang; Wang, Chunming; Li, Wuguo; Wang, Gangqiang; Chen, Wei; He, Yulong; Zhang, Changhua
Abstract: Background: N6‐methyladenosine (m6A) methylation, a well‐known modification with new epigenetic functions, has been reported to participate in gastric cancer (GC) tumourigenesis, providing novel insights into the molecular pathogenesis of GC. However, the involvement of Wilms' tumour 1‐associated protein (WTAP), a key component of m6A methylation, in GC progression is controversial. Here, we investigated the biological role and underlying mechanism of WTAP in GC. Methods: We determined WTAP expression using tissue microarrays and The Cancer Genome Atlas (TCGA) data set, which was used to construct co‐expression networks by weighted gene co‐expression network analysis (WGCNA). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed by Database for Annotation, Visualization and Integrated Discovery (DAVID). CIBERSORT was used to determine WTAP expression in 22 immune cell types. Results: Wilms' tumour 1‐associated protein was highly expressed in GC, which indicated a poor prognosis, and WTAP expression served as an independent predictor of GC survival. By WGCNA, GO, KEGG and core gene survival analyses, we found that high WTAP expression correlated with RNA methylation and that low expression correlated with a high T cell–related immune response. CIBERSORT was used to correlate low WTAP expression with T lymphocyte infiltration. Conclusion: RNA methylation and lymphocyte infiltration are the main causes of high WTAP expression and poor prognosis, respectively.